Analysis of The Influence of Tangibles, Empathy, Responsiveness of Service Quality on Student Parents Satisfaction - yesi suhartini (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2023)
Service quality is very important for service companies to face competition in the field of service companies, service quality by prioritizing satisfaction is a reliable strategy in developing service companies, in this study service quality includes the dimensions of tangibles, empathy, reliability, responsiveness, assurance, satisfaction in this study the satisfaction of parents of students who purchase services at the Nabila's House tutoring institution, this research method uses the correlation coefficient test, the determination coefficient, regression analysis with path analysis, the sample used in this study is a population of 142 parents of students. The results of this study prove that partially tangibles, reliability, and responsiveness have a significant effect on the satisfaction of parents of students as well as simultaneously, the quality of service in this study contributed 80.60% in explaining the satisfaction of parents of students.